Tindak Pidana Pembunuhan Studi Kasus Pengadilan Negeri Gorontalo Berdasarkan Analisis Kekuatan Autopsi Sebagai Alat Bukti - Nur’ Ain Tomayahu; Suwitno Yutye Imran; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
Legislation regarding judicial examination procedures requires forensic experts, article 133 of the Criminal Procedure Code paragraph (1), explains that in the case of an investigator for the purposes of justice regarding a victim who has been injured, poisoned or died allegedly because of an incident which constitutes a criminal act, the judiciary has the authority to submit a request expert information. In medical experts, justice and other experts. Why do you need a forensic doctor? Because it is impossible for investigators, judges, prosecutors to know all the knowledge in the field of medicine which will later be used to deal with criminal cases related to the human body, for example: violence, murder, suicide. With this, the authorities will ask for help from a doctor as an expert witness, the doctor's testimony as an expert witness, the doctor's testimony is regulated by law. In handling murder cases, a forensic autopsy is needed which will provide clear information regarding criminal cases. Accordingly, a forensic autopsy will produce tools that can be used as evidence in deciding a case by a judge. With a forensic autopsy, the cause of a person's death will be known. Therefore, an autopsy is very much needed in the investigation of criminal acts of murder and during the trial process. This research aims to understand the process of proving the criminal act of murder in the Gorontalo District Court with case number 61/PID.B/2023/PN.GTO. and the use of autopsy evidence in the process of proving this research is analyzed normatively, namely research that analyzes the reciprocal relationship between legal facts and social facts which can be seen as independent variables and social facts as dependent variables. murder that was not accompanied by an autopsy.